- - Misseroni Raddatz, Adelio (Acta Bioethica, 2000)
Given the conceptual confusion that exists about the term euthanasia, the objective of this monograph consists of elucidating the sense and reach of this expression, from a legal and penal perspective, and by so doing, determine what behaviors are legally relevant and which should be necessarily excluded from the ius poniendi ambit. As a next step, the author analyses the determining elements of the euthanistic behavior, always considered from a penal perspective. Once the reach of the expression is determined, it is possible to analyze such behavior from the perspective of its objective classification for an ulterior brief reviewing of some Latin American normatives that clearly typify such behaviors. Finally, the ethical and legal feasibility of a legislation properly euthanistic will be analysed in the light of the principle of human dignity , explicitly or implicitly recognized by the main international instruments and by all the political codes of the social and democratic States of right.